RESOURCE AND ORGANIZATIONAL ENSURING THE DEVELOPMENT OF RETAIL TRADE ENTERPRISES - HAVRYLCHENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes current research related to resource and organizational support for the development of retail trade enterprises. A typology of the instrumental content of the enterprise management system has been developed, which provides a basis for making the right management decisions. The definition of the resource management mechanism of the enterprise is proposed, the difference of which is that it takes into account the interests (motivations) of the enterprise, the consumer and society, identifies the key components of management and establishes relationships between management subsystems based on the signs of belonging (by qualitative and quantitative characteristics) to those or other resources. The classification of the main models of resource management depending on the type of resource is systematized. It is substantiated that resource balance should be reflected in the construction of a rational interaction between various subsystems of enterprise management. It was established that the resource management mechanism of the enterprise should include the tools of management activity of the business entity, distributed among subsystems (financial, material, labor), which act as a single entity and interact with each other through the implementation of the functions of use, distribution, availability, and replenishment of the enterprise's resources , which allows us to consider it as a key link in the enterprise management system in a competitive environment. The resource potential of the business entity is studied as its ability to form, develop and actively use tangible and intangible assets to ensure sustainable competitive advantages in market conditions. The considered mechanism of organizational and economic interaction of the processes of using structural components of resource potential determines the strategic orientation of the economic entity and thereby establishes the necessary level of economic efficiency of its operation on the market.
Keywords: resource support; organizational support; enterprise; enterprise development; enterprise potential; innovative development strategies; retail enterprises